Social theories and Social Service: analysis on the condition of Social Service in the Metropolitan Region of Belém/PA - Tabaranã Silva, Olga Myrla (Textos & Contextos (Porto Alegre), 2023)
The objective of this article is to reflect on the processes of theoretical incorporation in the professional environment of Social Work and its consequences in contemporary training and performance. As well as reflecting on strategies for valuing the intention to break with the conservative tradition in which the profession was created. For this, we used bibliographic reference and empirical material from data collected in the last research of the Group of Studies in Social Work, Professional Formation and Social Policy (GEPSS/UFPA), of which we are part. The lines that illustrate our analysis come from semi-structured interviews with professionals trained under the aegis of the new Curriculum Guidelines at UFPA and at private universities both on-site and at a distance. We conclude this article with the definition that neoconservatism or postmodernity has significant influences on our formation, but that do not go beyond the need for knowledge and appreciation of the intention of rupture. This indicates the urgency of highlighting this antagonistic debate in the professional sphere in order to strengthen the profession, which has historically taken a critical position.